2001
DOI: 10.1177/016146810110300703
|View full text |Cite
|
Sign up to set email alerts
|

Chapter III: A Shifting Social Context: NSSE Looks at Equity in Schools and Classrooms

Abstract: The issue of equity is an important thread running through a century of Yearbooks of the National Society for the Study of Education (NSSE). Although we tend to think of equity in the schools as a relatively recent issue, it was a major concern as early as 1916. This chapter analyzes how authors of NSSE chapters conceptualized and wrote about equity in U.S. schools.Equity denotes equality of educational opportunities and outcomes for all students. Although much has been made elsewhere of the difference between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…In exploring the effectiveness of this project, Battistich and colleagues (see Battistich, Solomon, Watson, & Schaps, 1997, for a review of this work) found that caring was linked with more positive prosocial attitudes and altruistic behaviors, greater concern for others, greater perspective taking, higher levels of social competence, and less delinquency. Social–emotional theorists also believe that social–emotional competencies can best be fostered in a caring, safe, and responsive context (Cohen, 2001; Comer, 2003; Payton et al, 2000). For instance, social–emotional learning programs have been positively related to indices of prosocial behavior, such as social–emotional competence (Elias, Gara, Schuyler, Branden-Muller, & Sayette, 1991).…”
Section: Caring Climatementioning
confidence: 99%
“…In exploring the effectiveness of this project, Battistich and colleagues (see Battistich, Solomon, Watson, & Schaps, 1997, for a review of this work) found that caring was linked with more positive prosocial attitudes and altruistic behaviors, greater concern for others, greater perspective taking, higher levels of social competence, and less delinquency. Social–emotional theorists also believe that social–emotional competencies can best be fostered in a caring, safe, and responsive context (Cohen, 2001; Comer, 2003; Payton et al, 2000). For instance, social–emotional learning programs have been positively related to indices of prosocial behavior, such as social–emotional competence (Elias, Gara, Schuyler, Branden-Muller, & Sayette, 1991).…”
Section: Caring Climatementioning
confidence: 99%
“…A danger is that teachers may misinterpret explicit instruction to mean drill and practice through didactic instruction and, thus, fail to promote critical and creative thinking with diverse students. This could become yet another stereotype that can potentially limit opportunities for diverse students to learn to function competently in the mainstream (see Cohen, 2001, for a historical context). Instead, students from diverse backgrounds need to be provided with learning opportunities to explore and construct meanings based on what they bring to the learning process.…”
Section: Research Agendamentioning
confidence: 99%
“…Status was measured using a sociometric instrument inspired by Cohen and Lotan (1997) at the beginning and end of the school year. In determining status among peers, local characteristics, such as academic status and popularity are significant factors ( Lotan, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Equal status is needed to facilitate participation of all in academic tasks ( Cohen, 1994 ; Pescarmona, 2015 ), to develop inclusive education in heterogeneous classrooms ( Cohen, 1994 ; Lotan, 2006 ; Pescarmona, 2014 ; Lotan and Holthuis, 2021 ; Lotan, 2022 ) and to give voice to diversity ( Pescarmona, 2023 ). It requires fostering the participation and learning of those who have lower initial status ( Cohen and Lotan, 1997 ). This is particularly crucial and challenging for students who have not yet acquired all the social and/or academic skills or have limited mastery of the language of instruction ( Cohen et al, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation